Why are educated and risk-loving persons more mobile across regions? - Stefan Bauernschuster; Oliver Falck; Stephan Heblich; Jens Südekum (Institute for the Study of Labor (IZA), 2012)
Why are better educated and more risk-friendly persons more mobile across regions? To answer this question, we use micro data on internal migrants from the German Socio- Economic Panel (SOEP) 2000-2006 and merge this information with a unique proxy for region-pair-specific cultural distances across German regions constructed from historical local dialect patterns. Our findings indicate that risk-loving and skilled people are more mobile over longer distances because they are more willing to cross cultural boundaries and move to regions that are culturally different from their homes. Other types of distance-related migration costs cannot explain the lower distance sensitivity of educated and risk-loving individuals.
Keywords: J61; R23; D81; 330; migration; culture; distance; human capital; risk attitudes; Binnenwanderung; Risikofreude; Bildungsniveau; Kulturelle Identität; Entfernung; Deutschland